Unconventional Computation and Natural Computation 13th International Conference, UCNC 2014, London, ON, Canada, July 14-18, 2014, Proceedings - Ibarra, Oscar H.; Kari, Lila.; Kopecki, Steffen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 13th International Conference on Unconventional Computation and Natural Computation, UCNC 2014, held in London, ON, Canada, in July 2014. The 31 revised full papers were carefully reviewed and selected from 79 submissions. The papers cover a wide range of topics including among others molecular, quantum, optical and chaos computing as well as neural computation, evolutionary computation, swarm intelligence and computational neuroscience.
Five Nodes Are Sufficient for Hybrid Networks of Evolutionary Processors to Be Computationally Complete -- Learning Two-Input Linear and Nonlinear Analog Functions with a Simple Chemical System -- Scaled Tree Fractals Do not Strictly Self-assemble -- GUBS a Language for Synthetic Biology: Specification and Compilation -- Modeling Syntactic Complexity with P Systems: A Preview -- Simulating Cancer Growth Using Cellular Automata to Detect Combination Drug Targets -- Towards an MP Model for B Lymphocytes Maturation -- Pseudo-inversion on Formal Languages -- Reverse-Engineering Nonlinear Analog Circuits with Evolutionary Computation -- Steps toward Developing an Artificial Cell Signaling Model Applied to Distributed Fault Detection -- Dynamic Adaptive Neural Network Array -- Unconventional Arithmetic: A System for Computation Using Action Potentials -- Reservoir Computing Approach to Robust Computation Using Unreliable Nanoscale Networks -- On DNA-Based Gellular Automata -- Doubles and Negatives are Positive (in Self-assembly) -- On String Languages Generated by Sequential Spiking Neural P Systems Based on Maximum Spike Number -- Languages Associated with Crystallographic Symmetry -- An Energy-Efficient Computing Approach by Filling the Connectome Gap -- Fast Arithmetic in Algorithmic Self-assembly -- Pattern Formation by Spatially Organized Approximate Majority Reactions -- Mecobo: A Hardware and Software Platform for in Materio Evolution -- Compact Realization of Reversible Turing Machines by 2-State Reversible Logic Elements -- Universal Computation in the Prisoner’s Dilemma Game -- Exact Simulation of One-Dimensional Chaotic Dynamical Systems Using Algebraic Numbers -- Artificial Astrocyte Networks, as Components in Artificial Neural Networks -- Quantum, Stochastic, and Pseudo Stochastic Languages with Few States -- Phase Transition and Strong Predictability -- PHLOGON: PHase-Based LOGic Using Oscillatory Nano-Systems -- Size-Separable Tile Self-assembly: A Tight Bound for Temperature-1 Mismatch-Free Systems -- Development of Physical Super-Turing Analog Hardware.
Keywords: Computers; Pattern recognition; Artificial intelligence; Computation by Abstract Devices; Theory of Computation; Pattern Recognition; Artificial Intelligence